Flash pulmonary oedema secondary to persistent left superior vena cava - Demirjian, Jack; Divecha , Rohan; Garrastegui Mercado , Emmanuel; Garcia, Oscar (European Journal of Case Reports in Internal Medicine, 2023)
Persistent left superior vena cava (PLSVC) is a common congenital anomaly of the thoracic venous system. It is usually asymptomatic and is detected when cardiovascular imaging is performed for unrelated reasons. Its presence can complicate catheter placement within the right side of the heart, as well as cardiac procedures. In most cases PLSVC can go unnoticed and only becomes pertinent when patients require cardiac imaging or surgery. Once found, it puts patients at risk for cardiac interventions. Here we present a case that highlights the practical implications of PLSVC where a patient developed flash pulmonary oedema after gastrointestinal procedures – in this case, laparoscopic cholecystectomy – as well as endoscopic retrograde cholangiopancreatography (ERCP). Management is also discussed, leading to the resolution of symptoms. The report will also propose a pathophysiologic mechanism leading to this complication that is not well understood in the medical literature.